A Successful Anticoagulation Protocol for the First HeartMate® II Implantation in the United States - Amir, Offer (2005)
Bleeding and thrombus formation are common problems with life-threatening implications in patients receiving a left ventricular assist device. We describe the anticoagulation protocol for the 1st patient in the United States to undergo successful implantation of the HeartMate® II left ventricular assist system.